Financial forecasting using meta-cognitive fuzzy neural networks - Singh Akhand Pratap (2014)
Financial Markets have been attractive due to the thrill they provide through the profits or losses on the investments made in them. With the levels of achievements made in the field of Machine Learning and predictive mechanisms, there is a hope to finally break down the mystery of the financial markets through such machine learning techniques.